2011
DOI: 10.2478/v10038-011-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Drop Jump Potentiation Protocol on Sprint and Countermovement Vertical Jump Performance

Abstract: Purpose. Muscle post-activation potentiation (PAP) is a mechanism by which power twitch is increased after previous conditioning contractions. In this study, we determined the time-dependent effect of a loaded drop-jump protocol on sprint time and countermovement jump height in well-trained athletes. Methods. Ten athletes randomly performed the control and experimental protocols on two different days. As a pre-test, the athletes performed the vertical jump and 50 m sprint test for preload measurements. Then, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 29 publications
4
25
1
7
Order By: Relevance
“…This study demonstrated that PLY provides a more efficient method of inducing potentiation than RES. The results of our study are in agreement with those of previous studies which showed that sprint performance was improved after PLY [ 40 , 41 ]. Sprint performance improvement after RES was also demonstrated by other previous studies [ 21 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrated that PLY provides a more efficient method of inducing potentiation than RES. The results of our study are in agreement with those of previous studies which showed that sprint performance was improved after PLY [ 40 , 41 ]. Sprint performance improvement after RES was also demonstrated by other previous studies [ 21 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…The improvement of post-exercise CMJ performance (PAP) registered in this study confirms the results obtained in similar studies conducted previously ( Bomfim Lima et al, 2011 ; Boullosa and Tuimil, 2009 ; Boullosa et al, 2011 ; García-Pinillos et al, 2015 ), where significant differences were found after completion of the running test compared to baseline values. Regarding handgrip strength, as indicated in Paavolainen et al (1999) , the decreased muscular force in those muscles not involved in the exercise (handgrip strength) revealed supraspinal fatigue.…”
Section: Discussionsupporting
confidence: 92%
“…Byrne et al [27] verified that a brief warm-up of 5 min of running, dynamic stretches and three vertical jumps resulted in 5% better performance in 20 m sprint compared to the warm-up without the jumps. Accordingly, Lima et al [45] found that 2 × 5 jumps from a height of 0.75 m caused 2% faster 50 m sprint performance. More recently, Turner et al [44] found that the utilization of alternate-leg plyometric bounding provided an effective strategy for acutely improving sprint acceleration performance (10 and 20 m).…”
Section: Discussionmentioning
confidence: 99%